Multicenter Evaluation of a Gradient Diffusion Method for Antimicrobial Susceptibility Testing of Helicobacter pylori - Salika M. Shakir; Joshua Otiso; George Keller; Hillary Van Heule; Lucas J. Osborn; Nicolynn Cole; Audrey N. Schuetz; Sandra S. Richter; Marc Roger Couturier (Microbiology Spectrum, 2022)
ABSTRACT Helicobacter pylori is an important human pathogen associated with peptic ulcer disease, dyspepsia, and gastric malignancy. Antimicrobial susceptibility testing (AST) is often requested for patients who fail eradication therapy. The Clinical and Laboratory Standards Institute (CLSI) reference method, agar dilution (AD), is not performed in most laboratories and maintaining organism viability during transit to a reference laboratory is difficult. We assessed the performance of the Etest (bioMérieux) as a method for H. pylori AST in comparison to AD. Etest MICs were determined for 83 H. pylori isolates at ARUP and Cleveland Clinic (CC). Categorical agreement (CA), very major, major, and minor errors (VME, ME, and mE) were determined for Etest using AD performed at Mayo Clinic Laboratories as the reference method. Testing on isolates with errors was repeated to determine final results summarized below. For clarithromycin, 66.3% of isolates were resistant (R) by AD; Etest results at each laboratory showed 1mE (1.2%) and 1 ME (3.8%). For tetracycline, only 2 isolates were R by AD; a single VME occurred at both sites (98.8% CA, 50% VME) with the same isolate. Applying EUCAST levofloxacin breakpoints to interpret ciprofloxacin results, 60.2% of isolates were R by AD; ARUP CA was 97.6% (1 ME (3%), 1 VME (2%)) and CC CA was 96.3% (1 ME (3%), 2 VMEs (4%)). Despite high error rates, the categorical agreement was acceptable (>90%) for all three antibiotics between AD and Etest. In-house susceptibility testing by gradient diffusion can allow for testing of fastidious organisms that may not survive transport to specialized laboratories; however, the method is not without technical challenges. Characterization of resistance mechanisms, increased AD dilutions, and testing from the same inoculum may determine if the observed errors reflect technical issues or breakpoints that need optimization. IMPORTANCE Routine antimicrobial susceptibility testing (AST) of Helicobacter pylori by agar dilution is difficult to perform and not practical in most clinical microbiology laboratories. The Etest gradient diffusion method can be a reliable alternative for H. pylori AST with the advantage of being a less laborious quantitative method. This work reveals that an optimized Etest method can provide acceptable performance for H. pylori AST and describes the challenges associated with this methodology.